1996
DOI: 10.1021/om950807d
|View full text |Cite
|
Sign up to set email alerts
|

95Mo NMR Studies on Cationic Phosphenium Complexes of Molybdenum

Abstract: The 95Mo NMR spectra of cationic molybdenum phosphenium complexes have been measured. Going from fac-[(bpy)(CO)3Mo{PN(Me)CH2CH2NMe(OMe)}] (1a) to fac-[(bpy)(CO)3Mo{PN(Me)CH2CH2NMe}]+ (fac-1b) to mer-[(bpy)(CO)3Mo{PN(Me)CH2CH2NMe}]+ (mer-1b) causes deshielding of the 95Mo doublet resonance (δ −1081 (1a), −1049 (fac-1b), −1015 (mer-1b)), an increase in the Mo−P coupling constant (193 Hz (1a), 264 Hz (fac-1b), 337 Hz (mer-1b)), and an increase in the line width (35 Hz (1a), 90 Hz (fac-1b), 300 Hz (mer-1b)). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Therefore, the formation of cis-Mo(CO) 4 {P(OMe) 3 }{P(OMe) 2 F} was proposed. The similar OR/F substitution reaction has been reported [6,9,11]. The 31 P NMR spectrum after 24 h, signals due to cis-Mo(CO) 4 -{P(OMe) 3 }{P(OMe) 2 F} increased in intensity and a new singlet at 173.4 ppm attributable to trans-5 was observed.…”
Section: Reaction Of Fac-mo(co) 3 L 3 and Cis-mo(co) 4 L 2 With Bf 3 supporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, the formation of cis-Mo(CO) 4 {P(OMe) 3 }{P(OMe) 2 F} was proposed. The similar OR/F substitution reaction has been reported [6,9,11]. The 31 P NMR spectrum after 24 h, signals due to cis-Mo(CO) 4 -{P(OMe) 3 }{P(OMe) 2 F} increased in intensity and a new singlet at 173.4 ppm attributable to trans-5 was observed.…”
Section: Reaction Of Fac-mo(co) 3 L 3 and Cis-mo(co) 4 L 2 With Bf 3 supporting
confidence: 79%
“…(1) [4,5]. This method is applicable for many types of transition 3 {P(NMeCH 2 ) 2 (OR)} [6][7][8][9][10][11][12], M(dppe)(CO) 3 {P(NMeCH 2 ) 2 (OR)} [7], M(bpy)-(CO) 2 {P(NMeCH 2 ) 2 (OR)} 2 [8,11,12], M(CO) 3 {P(NMe-CH 2 ) 2 (OR)} 3 [13], M(CO) 4 {P(NMeCH 2 ) 2 (OR)} 2 [13], CpM(CO) 2 (ER 3 ){P(NMeCH 2 ) 2 (OR)} (M = Cr, Mo, W) [14][15][16][17], and CpM(CO)(ER 3 ){P(NMeCH 2 ) 2 (OR)} (M = Fe, Ru) (ER 3 = CH 3 , SiMe 3 , GeMe 3 , SnMe 3 ) [10,[18][19][20][21][22][23]. Systematic researches for reactions of Mo(bpy)-(CO) 3 {PXY(OR)} with BF 3 Á OEt 2 revealed the effect of the substituents (X, Y) on the stability of cationic phosphenium complexes; the stability increases with increasing the number of amino substituents on the phosphenium phosphorus [9].…”
Section: Introductionmentioning
confidence: 99%
“…BF 3 induces migratory insertion of the CO ligand into the Fe-Me bond followed by an Arbuzov-like dealkylation with F -to give the corresponding  1 -P−phosphonate complex 118 which is converted by PPh 3 addition into 119 incorporating a bond between the phosphonate oxygen and the boron atoms in its structure [220]. The reaction of  1 -P−phosphonate iron complex 120 with the hydroborane 9-BBN proceeds readily and quantitatively at room temperature resulting in the formation of the corresponding formyl complex 121.…”
Section: Miscellaneous Prevalent Activitiesmentioning
confidence: 99%
“…Scheme 39.Reduction of CO ligand of  1 -P−phosphonate iron complexes 117[220] and 120[221] with boron reagents.An halogenation reaction of an amidophosphonato ligand grafted on an iron metallic fragment was reported. Addition of boron trihalides BCl 3 on P-metalated amidophosphonate complex 122 allowed the synthesis of the corresponding halogenated  1 -P−amidophosphonate complexes 123 and 124 which are good precursors for future functionalization on the organophosphorus ligand (Scheme 40,[222]) .Scheme 40.Halogenation reaction of the  1 -P−amidophosphonato ligand in iron complex 122[222].Taking into account the unique properties of O−anionic monodentate and bidentate  1 -P−phosph(in)ito ligands presented in this review, the results recently reported on the O,P-metalated phosphinite trinuclear complex 125 in which the six {Ph 2 P−O} arms bridge the Ti center with the two terminal Pd atoms[223].…”
mentioning
confidence: 99%